2009
DOI: 10.1271/bbb.90104
|View full text |Cite
|
Sign up to set email alerts
|

Isolation ofPseudomonassp. Strain HB01 Which Degrades the Persistent Brominated Flame Retardant γ-Hexabromocyclododecane

Abstract: In this study, we isolated Pseudomonas sp. strain HB01 from a soil sample contaminated with brominated pollutants, and found that it degraded -hexabromocyclododecane (-HBCD). The strain degraded 81% of 1 mM -HBCD within 5 d of culture. Furthermore, it demonstrated biodegradation of structurally related (bromo) alkanes. To the best of our knowledge, this is the first report that outlines the isolation of a bacterial strain that degrades -HBCD.Key words: hexabromocyclododecane; brominated flame retardants; Pseud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 10 publications
2
9
1
Order By: Relevance
“…A strain of Pseudomonas sp. has been reported that it degraded 81% of 1 mM c-HBCD within 5 days treatment (Yamada et al, 2009). However, in this study, a pure culture of Achromobacter sp.…”
Section: Introductioncontrasting
confidence: 59%
“…A strain of Pseudomonas sp. has been reported that it degraded 81% of 1 mM c-HBCD within 5 days treatment (Yamada et al, 2009). However, in this study, a pure culture of Achromobacter sp.…”
Section: Introductioncontrasting
confidence: 59%
“…The dibromocyclododecadiene (DBCD, 322 m/z), a typical debromination product, was detected using UHPLC/Q-TOF-MS during reactive process (Supplementary Figure S1 ). Comparison of HBCD biodegradation and bromide generation, it could be deducted that bromide released from HBCD reduction by debromination process, which was consistent to the previous reports ( Yamada et al, 2009 ). Transformation and correlation of VSS and TOC indicated that on the one hand, during 12 days cultivation, microbial growth experienced lag phase, log phase, and stationary phase, sequentially ( Figure 2F ; Fang and Jia, 1999 ); on the other hand, the biodegradation process with the generation of bromide was significantly negative correlated with the TOC analysis.…”
Section: Resultssupporting
confidence: 91%
“…The previous report about the acclimation of microbial communities to mineralize the organic compounds indicated that some of enriched microorganism may be utilized to degrade the treated hazardous materials ( Xiao and Roberts, 2013 ). Based on this, it can be speculated that the microbial enriched during the HBCD acclimated process may have a potential capability of degrading HBCD, just like Pseudomonas , which has been described previously ( Yamada et al, 2009 ).…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…HB01 [45]. Since bromide atom was not detected after degradation reaction, such transformation might not through haloelimination.…”
Section: Aerobic Oxidative Degradationmentioning
confidence: 97%